Laki-Laki Usia 20 Tahun dengan Open Fraktur 1/3 Proksimal Tibia Fibula Sinistra, Open Fraktur Metatarsal Pedis Sinistra, Closed Fraktur Phalanx Distal, dan Radius Distal Sinistra (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Open fractures are serious orthopedic injuries with a high risk of infection and soft tissue complications. A 20-year-old male patient presented to the Emergency Department with severe pain in his left leg and wrist, accompanied by a laceration on his face, following a traffic accident. Physical examination revealed deformity and an open wound on the left leg, along with severe swelling and tenderness. Radiographic results showed an open fracture of the proximal third of the left tibia and fibula, an open fracture of the left pedal metatarsal, a closed fracture of the distal phalanx of the third digit of the left foot, and a closed fracture of the distal third of the left radius with distal radioulnar joint dislocation. Based on the Gustilo–Anderson classification, the case was categorized as type IIIB. The patient received initial management including debridement, broad-spectrum antibiotics, analgesics, and splinting. Surgical intervention was performed in stages, comprising Open Reduction External Fixation (OREF) for the tibia–fibula and left foot, followed by Open Reduction Internal Fixation (ORIF) for the distal left radius. Postoperative evaluation showed clinical improvement with reduced pain, decreased edema, and improved extremity function. This case emphasizes the importance of rapid and appropriate management of multiple open fractures to prevent infection, maintain bone stability, and accelerate the healing process.